ChemInform Abstract: High‐Resolution Structural Characterization of Two Layered Aluminophosphates by Synchrotron Powder Diffraction and NMR Crystallographies. Issue 34 (1st August 2013) - Bouchevreau, Boris; Martineau, Charlotte; Mellot‐Draznieks, Caroline; Tuel, Alain; Suchomel, Matthew R.; Trebosc, Julien; Lafon, Olivier; Amoureux, Jean‐Paul; Taulelle, Francis
Abstract The structures of (enH2)2 [Al5(OH)(PO4)3 (PO3OH)4]·2H2O and (enH2)2 [Al5(PO4)5(PO3OH)2] ·H2O are determined by powder synchrotron XRD and solid state NMR spectroscopy.